2014
DOI: 10.32473/edis-in1027-2014
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Honey Bee Exposure to Pesticides

Abstract: Protecting honey bees and other pollinators from pesticide impacts is important to the sustainability of agriculture. Consequently, pesticide applicators must determine if there is a clear hazard to managed or wild populations of bees. Potential exposure of bees to pesticides can vary greatly depending on the type of pesticide, formulation, application method, label restrictions, and other factors. The goal in using a pesticide is to achieve maximum benefit (success) with minimum negative impact, and these fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Therefore, within a radius of 5 miles (8 km) around the hive, an actively feeding colony can cover a territory up to 80 miles (201 km 2 ) in size. Bees are more likely to come into contact with pesticides and other environmental contaminants in the foraging area during foraging hours and at the sites of interaction (flora, pollen, nectar, water and propolis) (Ellis et al, 2014) (Fig. 2).…”
Section: Routes Of Pesticide Exposurementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, within a radius of 5 miles (8 km) around the hive, an actively feeding colony can cover a territory up to 80 miles (201 km 2 ) in size. Bees are more likely to come into contact with pesticides and other environmental contaminants in the foraging area during foraging hours and at the sites of interaction (flora, pollen, nectar, water and propolis) (Ellis et al, 2014) (Fig. 2).…”
Section: Routes Of Pesticide Exposurementioning
confidence: 99%
“…Dust is more dangerous than liquid formulations. This is because these chemicals can drift with air currents and reach and penetrate bee colonies (Ellis et al, 2014).…”
Section: Pesticide Management Techniques To Reduce Bee Losses To Ensu...mentioning
confidence: 99%
“…Although the putative causes of colony loss are still unclear, the combined efects of climate change, intensive agriculture, pesticides use, pest and pathogens, and biodiversity loss are some risk factors for global honeybee loss [12]. Earlier reports suggested that the extensive exposure of bees to pesticide incidents would possibly be a major factor for honeybee loss and colony decline [13][14][15][16][17]. In Ethiopia, widespread reports indicate that exposure to commonly used agricultural pesticides has been linked to the dramatic honeybee deaths and colony decline than any other factors in the country [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%